1997
DOI: 10.1121/1.420354
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the effect of cochlear-implant electrode insertion depth on speech understanding

Abstract: Normally hearing listeners were presented with vowels, consonants, and sentences for identification through an acoustic simulation of a five-channel cochlear implant with electrodes separated by 4 mm (as in the Ineraid implant). The aim of the experiment was to simulate the effect of depth of electrode insertion on identification accuracy. Insertion depth was simulated by outputting sine waves from each channel of the processor at a frequency determined by the cochlear place of electrodes inserted 22-25 mm int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
146
1
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(166 citation statements)
references
References 6 publications
9
146
1
6
Order By: Relevance
“…Both hybrid and traditional implant patients note that speech through their implant initially sounds Bsqueaky^, but later sounds more normal and like regular speech [Dorman et al 1997;personal observations]. This again suggests that implant processors commonly assign speech frequencies to the wrong frequency-place locations, although the mismatch would be much smaller for traditional implant patients.…”
Section: Mechanisms Of Electric Pitch Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both hybrid and traditional implant patients note that speech through their implant initially sounds Bsqueaky^, but later sounds more normal and like regular speech [Dorman et al 1997;personal observations]. This again suggests that implant processors commonly assign speech frequencies to the wrong frequency-place locations, although the mismatch would be much smaller for traditional implant patients.…”
Section: Mechanisms Of Electric Pitch Shiftsmentioning
confidence: 99%
“…Correct allocation of acoustic frequencies to individual electrodes may be important for music and speech recognition (Dorman et al 1997;Fu and Shannon 1999a,b;Faulkner et al 2003;Baskent and Shannon 2004), although some studies suggest that implant users can adapt over time to spectrally shifted speech-frequency mappings (Rosen et al 1999;Fu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have been directed toward providing a better understanding of the role of electrode location and spacing on various perceptual attributes of hearing with a CI (Blamey et al 1996;Ketten et al 1998;Pfingst et al 2001;Skinner et al 2002;Yukawa et al 2004;Baumann and Nobbe 2006;Boex et al 2006). Several psychophysical studies have shown that spectral distortions such as apical or basal shift (Dorman et al 1997;Fu and Shannon 1999), nonlinear warping (Shannon et al 1998), and compression or expansion of the applied frequency map Shannon 2003, 2004) decrease speech perception, thus suggesting that an optimum fit of the frequency map for a given electrode position may significantly improve the performance of the CI listener. Although some studies have shown that speech perception with a frequency-shifted implant map can substantially improve with auditory training and if the patient has more time to adapt to the map (Rosen et al 1999;Fu et al 2005), an initial optimum frequency fit may provide immediate benefit for implant recipients and a better basis for the subsequent adaptation that occurs in most CI users.…”
Section: Introductionmentioning
confidence: 99%
“…formants, will be misrepresented. A misrepresentation of frequency, depending on severity, should cause (1) difficulties in adapting to electrical stimulation, (2) a low asymptote for performance, or (3) both (see, for example, Skinner et al 1995;Dorman et al 1997;Fu and Shannon 1999a, b;Fu et al 2002;Dorman and Ketten 2003;Rosen et al 1999).…”
mentioning
confidence: 99%